Spatial control of branching within dendritic arbors by dynein-dependent transport of Rab5-endosomes. - Satoh, D.; Sato, D.; Tsuyama, T.; Saito, M.; Ohkura, H.; Rolls, M.M.; Ishikawa, F.; Uemura, T. (Nature Cell Biology, 2008)
Dendrites allow neurons to integrate sensory or synaptic inputs, and the spatial disposition and local density of branches within the dendritic arbor limit the number and type of inputs. Drosophila melanogaster dendritic arborization (da) neurons provide a model system to study the genetic programs underlying such geometry in vivo. Here we report that mutations of motor-protein genes, including a dynein subunit gene (dlic) and kinesin heavy chain (khc), caused not only downsizing of the overall arbor, but also a marked shift of branching activity to the proximal area within the arbor. This phenotype was suppressed when dominant-negative Rab5 was expressed in the mutant neurons, which deposited early endosomes in the cell body. We also showed that 1) in dendritic branches of the wild-type neurons, Rab5-containing early endosomes were dynamically transported and 2) when Rab5 function alone was abrogated, terminal branches were almost totally deleted. These results reveal an important link between microtubule motors and endosomes in dendrite morphogenesis.